Les hippodromes et les concours hippiques dans la grèce antique - Moretti, Jean-Charles; Valavanis, Panos (Suppléments du BCH, 2019)
Horse racing held a significant role in the Greek world, not only in the Olympic competitions, but in many other sporting events - local, regional or Panhellenic. This volume is the first study to exclusively investigate these races and hippodromes. This volume acknowledges the significant progress made in recent years in the analysis of iconographic representations and literary or epigraphic texts relating to hippic sports. It outlines new reproductions of already known racetracks, such as those of Olympia and the Lykaion, and presents newly identified tracks, such as those of Delphi or Epidaurus. Twenty-eight articles, coming out of an international conference held in Athens in 2016, reproduce in all their breadth and diversity, the place and the form of racetracks and horse racing in architecture, the figurative arts, poetry and the political, economic, social and religious history of the Greek world.